2021
DOI: 10.1111/oik.08539
|View full text |Cite
|
Sign up to set email alerts
|

Individual‐based networks reveal the highly skewed interactions of a frugivore mutualist with individual plants in a diverse community

Abstract: While plant-animal interactions occur fundamentally at the individual level, the bulk of research examining the mechanisms that drive interaction patterns has focused on species or population levels. In seed-dispersal mutualisms between frugivores and plants, little is known about the role of space and individual-level variation among plants in structuring patterns of frugivory and seed dispersal in a plant community. Here we use a zoocentric approach to examine how space and variation between individual plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Other factors not analysed here, such as secondary compounds, fruit accessibility or fruiting neighbourhood could also be affecting consumption patterns (Moermond & Denslow 1985; Cipollini & Levey 1997; Carlo et al . 2007; Tonos et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors not analysed here, such as secondary compounds, fruit accessibility or fruiting neighbourhood could also be affecting consumption patterns (Moermond & Denslow 1985; Cipollini & Levey 1997; Carlo et al . 2007; Tonos et al . 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These traits are well known to affect frugivory (Sallabanks 1993;Ortiz-Pulido et al 2007;Schupp et al 2019) and are as well related to the ontogeny, growth and size hierarchies in plant populations (Weiner & Solbrig 1984). Other factors not analysed here, such as secondary compounds, fruit accessibility or fruiting neighbourhood could also be affecting consumption patterns (Moermond & Denslow 1985;Cipollini & Levey 1997;Carlo et al 2007;Tonos et al 2021).…”
Section: Interaction Intensity Dominates Partner Effectivenessmentioning
confidence: 99%
“…Additionally, rather than intrinsic functional traits, plant-lemur interactions may be driven by extrinsic factors (e.g. plant richness, Tonos et al, 2021). Effects of plant traits on connectivity were smaller than lemur traits, possibly because we did not include feeding preference traits (e.g.…”
Section: Traits That Determine Connectivitymentioning
confidence: 99%
“…Although widely used in social network analyses, ERGMs have only recently been applied to ecological networks (e.g. Arroyo‐Correa et al, 2021; Fuzessy et al, 2022; Tonos et al, 2021). In this study, we extend previous ecological applications of ERGMs that focused on one trophic level, jointly analysing attributes of both trophic levels and incorporating phylogenetic effects to improve our understanding of plant–animal interactions in complex networks.…”
Section: Introductionmentioning
confidence: 99%
“…Tur et al (2014) suggested that individual flower visitor‐plant species pollen transport networks were more specialized than species–species networks, and generalist pollinator species often comprised specialist pollinator individuals. The two limited cases strongly suggest that pollination networks based on pollinator individual level could be more specialized than those based on pollinator species level (Araújo et al, 2011; Des Roches et al, 2018; Tonos et al, 2021), indicating that pollination networks based on pollinator individual level could fill the gap between high pollinator fidelity and the highly generalized pollination networks (Arceo‐Gómez et al, 2016; Lázaro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%